Mais que números: análise do perfil sociodemográfico de mulheres em situação de violência atendidas na delegacia da mulher de Sobral, Ceará. - Costa, Rebeca Tárcia (2023)
Although there is an growing social recognition about the violence against women and it’s weight, the lack of data and more precise indicators about this phenomenon, notarially about the analysis of the local profile of the victims, limits the construction of more precise diagnosis, as well as there must be evaluated the existing public policies and the development of new reducing acts. Yearning to aid the fill in this hole, a study was conducted about the sociodemographic profile of the women victim of violence registered in the Delegacia de Defesa da Mulher de Sobral, in the year of 2022. For this, it had been analyzed all the 800 occurrence reports made in 2022, those of which were selected 435 of whom spoke about domestic violence and/or sexual violence against women, taken place in the city, uniting urban and rural areas. The majority of the victims whom reports were efective were female (99,5%), cis(99,7%), heterosexual (98,2%) e their ages were between 5 and 101 years old; 74,5% were declared brown, the majority had studied until elementary school (51,8%). About half were in some type of paying activity (49,9%) and, about the nature of the fact, the most frequent violence were moral, with 59,5% of the total cases. With this research, it was possible to identify various social markers and analyze probables relations between them and the registered cases of genre violence in the city of Sobral, with exemples, that women who suffered physical violence were younger than those who suffered moral damage and that women victims of sexual violence had lower average ages when compared to other victims. Other important factor about the research was the realization of the emptiness from the reports by some social groups, such as cross-dresser women, lesbians and trans women, which points to the possible invisibility of this important piece, seeing the relevancy of Brazil in cases of “transfeminicide” in the world scenario.